PENGGUNAAN BAHAN RESIN SEBAGAI SEALER ADESIF PADA PENGISIAN SALURAN AKAR - Putu Rusmiany; Dewa Made Wedagama; Ni Pt Okta Kristia Dewi (Interdental: Jurnal Kedokteran Gigi, 2017)
Tooth decay might be maintained through a variety of treatments, root canal treatment is the common treatment for irreversible damage. In the present decade many offer various kinds of fillers and root canal sealers, but each filler and sealer has advantages and disadvantages. The aim of this study was to ensure that resin sealer has good properties to fill root canal. The function of the root canal filling material is to fill the root canal and eliminate all entrances between the periodontium and the root canal. However, to get the ideal cover material, in addition to the core filling material, a sealer material is also needed to cover the gap between gutta percha and the root canal wall. This literature review concluded that resin sealers have biocompatibility, may adhere to dentin and have better adhesive properties than other sealers.